2015
DOI: 10.2500/ajra.2015.29.4256
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Asystole as an Electrocardiographic Artifact during Microdebrider use in Functional Endoscopic Sinus Surgery

Abstract: Although other EKG artifacts have been reported in the literature, this is the first case report of an artifact that mimicked asystole that stemmed from microdebrider use. Improved awareness of this potential EKG artifact for both the surgeon and the anesthesiologist may prevent an unnecessary costly workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For instance, disturbances in cardiac monitoring equipment during microdebrider device use have been reported. Patadia et al 23 noted several false asystolic events during microdebrider use that resulted in an aborted procedure and costly diagnostic testing, ultimately thought to be due to electrical interference from a chassis leak. Other authors have noted apparent ventricular tachycardia on intraoperative electrocardiograms, also thought to be to electrical interference 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, disturbances in cardiac monitoring equipment during microdebrider device use have been reported. Patadia et al 23 noted several false asystolic events during microdebrider use that resulted in an aborted procedure and costly diagnostic testing, ultimately thought to be due to electrical interference from a chassis leak. Other authors have noted apparent ventricular tachycardia on intraoperative electrocardiograms, also thought to be to electrical interference 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large study on epistaxis characteristics, Comelli et al 25 reported a strong inverse correlation peak during wintertime. Finally, as an important cautionary tale to all endoscopic sinus surgeons, Patadia et al 26 described an interesting case of electrocardiograph artifacts that mimic asystole from microdebrider use during ESS.…”
mentioning
confidence: 99%